2004
DOI: 10.1299/jsmea.47.287
|View full text |Cite
|
Sign up to set email alerts
|

Effective Transmission of High Frequency Ultrasound into a Silicon Chip through a Polymer Layer

Abstract: In this paper, we describe an effective transmission method of high frequency ultrasound into a silicon chip via the polymer layers. The layer is inserted between water and the chip, and the pressure of about 0.1 MPa is applied to the contact interface between the layer and the chip. The polyvinylidene chloride and polyvinyl chloride layers of 9 µm thick bring the ultrasonic resonance between water and silicon, and the ultrasound in the frequency range of 20 to 80 MHz is transmitted into the chip more effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Figure 4 shows that the joints between the package substrate and the solder balls are clearly imaged in both cases. Figures 5(a) and (b) show the echoes obtained using the dry-contact ultrasonic technique with a 9 m thick polyvinylidene chloride (PVDC) film and that obtained using the conventional water immersion technique, respectively (Tohmyoh and Saka, 2004b). The sample is a flip chip package with a bare silicon chip.…”
Section: Principlementioning
confidence: 99%
See 2 more Smart Citations
“…Figure 4 shows that the joints between the package substrate and the solder balls are clearly imaged in both cases. Figures 5(a) and (b) show the echoes obtained using the dry-contact ultrasonic technique with a 9 m thick polyvinylidene chloride (PVDC) film and that obtained using the conventional water immersion technique, respectively (Tohmyoh and Saka, 2004b). The sample is a flip chip package with a bare silicon chip.…”
Section: Principlementioning
confidence: 99%
“…This matching phenomenon is treated in the next section. (Tohmyoh and Saka, 2004b) with the permission of The Japan Society of Mechanical Engineers.…”
Section: Principlementioning
confidence: 99%
See 1 more Smart Citation
“…14 Furthermore, it has been discovered experimentally that the signal intensity of ultrasound transmitted via a solid layer sometimes exceeds that achieved by water immersion due to the ultrasonic resonance that occurs between water, the layer, and the sample. 4, 15 Desilets et al have reported a design method for producing acoustic thindisk transducers, which is based on the use of quarter-wave matching layers between a piezoelectric material and the acoustic load, and the validity of their method has been verified by the experiments using ultrasound of up to several MHz in frequency. 16 Today, this method is widely used to design piezoelectric transducers for medical imaging.…”
Section: Introductionmentioning
confidence: 99%